Factors influencing the willingness to pay for entrance permit: the evidence from Taman Negara National Park - Samdin, Zaiton; Abdul Aziz, Yuhanis; Radam, Alias; Yacob, Mohd Rusli (Canadian Center of Science and Education, 2010)
Non-market techniques such as Travel Cost Method (TCM) and Contingent Valuation Method (CVM) are commonly used to estimate the economic benefits of outdoor recreation. This study applied the CVM, with Willingness to Pay (WTP) as the elicitation method, to investigate the pattern of willingness to pay among visitors of Taman Negara National Park (TNNP). In applying CVM, the respondents were asked on the maximum amount they were willing to pay to enter this park. Data were obtained using closed-ended questionnaires through interview. About 196 visitors were involved in the study. This study used multiple regressions (MR) to investigate factors that determine WTP for entrance permit in TNNP. This study found that the WTP was positively related to several important factors; and these factors include nationality, income, education and marital status. All these factors can help to explain the WTP for entrance permit at TNNP. Approach in determining WTP for entrance permit will help park authorities to be more financially self-sufficient. In addition, it will generate more income, and thus more efficiency in operating and maintaining the national parks.